El Simbolismo De Los Colores Y El Concepto De Identidad Nacional En Algunos Poemas De "Romancero Gitano" Del Poeta Español Federico García Lorca. - قاسم محمد هلال سليم ا. م. د. (lark, 2021)
In this investigation we have discussed many of the hidden meanings behind the colors that Lorca used in the gypsy romance, highlighting the symbolism of those synonyms that generally reflect the characteristics of the Spanish national identity, especially Andalusian, and it was like a mirror that reflected the popular cultural heritage rooted in the collective memory of society,which simulates the history and geography of that land and is consistent with all the details of the religious concepts represented in the Bible and the Catholic Church.